PEMBINAAN PENGELOLAAN LAHAN TEPI PANTAI BERDASARKAN ASPEK HUKUM DAN PENGEMBANGAN INDUSTRI - Iin Indriani; Sri Utaminingsih; Estiningsih Trihandayani; Muhamad Iqbal (LPPM Universitas Pamulang, 2020)
Coastal land is an important asset that must be maintained and utilized by its function. Efforts that can be made to improve and enhance the fertility of coastal land can be done by applying technology and having sufficient knowledge. lack of community understanding related to the legal aspects of managing coastal laha so that the impact of inhibition of innovations that can help the economy of the local community, therefore it is necessary to understand these legal restrictions to the local community as well as a variety of innovative inputs to utilize land for industrial development. This guidance is given to all the people in Kelurahan Untung Jawa Island as additional information regarding the use of coastal land based on legal aspects and industrial development. This activity is expected to increase community knowledge and insights regarding the law of coastal land management and also increase innovation to improve home industries that are able to provide additional income for the local community. The method used in this community service is counseling on legal awareness of the community relating to the limits of the authority of the beach that can be used as well as training on utilization related to production innovation. With this activity, each community is required to know the management of coastal land and understand how to enhance the development of the tourism industry that can be done by innovating the utilization and management of coastal land.Keywords: Utilization, Coastal Land, Industry